Effect of acupressure on smoking cessation in young smokers with nicotine dependence: A mixed methods study - Ying-Ying Zhang; Yi-Jie Liu; Yuan Wang; Chen Shen; Shi-Bing Liang; Nicola Robinson; Hai-Fa Qiao; Jian-Ping Liu (Integrative Medicine Research)
Background: Acupressure has been widely used to help people quit for a long time in China. This study explores the feasibility and effects of acupressure on smoking cessation in young smokers with nicotine dependence to inform policy and decision-making. Methods: This was a single-group study with a pre/posttest design. The participants received four weeks of auricular acupressure treatment, led by a registered acupuncturist. Smoking cravings, nicotine dependence, withdrawal symptoms, and number of cigarettes per day (CPD) were recorded before and after treatment. Changes in outcomes were analyzed at 2 weeks and 4 weeks using SPSS software version 22.0. Semi-structured interviews were conducted with the participants to explore their experiences and attitudes toward auricular acupressure. Thematic analysis was used to analyze the data. Results: A total of 20 participants completed this study. A significant reduction was observed in smoking cravings (F = 11.02, P < 0.05), nicotine dependence (F = 11.09, P < 0.05), withdrawal symptoms (F = 11.19, P < 0.05), and CPD (F = 19.03, P < 0.05) across sessions. Additionally, withdrawal symptoms decreased significantly from 2 weeks to 4 weeks (P < 0.05) of acupressure treatment. Three interrelated themes emerged from the interviews: personal and external resources, the psychological and physical effects of acupressure, and satisfaction with acupressure for smoking cessation. Conclusions: The quantitative and qualitative data suggest that acupressure maybe effectively decrease nicotine dependence and smoking cravings. However, this was a pilot and single-arm study, and these findings must be further verified. The study supports the feasibility and safety of introducing acupressure therapy for smoking cessation in young smokers.